Evolution of Conformation, Nanomechanics, and Infrared Nanospectroscopy of Single Amyloid Fibrils Converting into Microcrystals. Issue 2 (11th December 2020) - Adamcik, Jozef; Ruggeri, Francesco Simone; Berryman, Joshua T.; Zhang, Afang; Knowles, Tuomas P. J.; Mezzenga, Raffaele
Abstract: Nanomechanical properties of amyloid fibrils and nanocrystals depend on their secondary and quaternary structure, and the geometry of intermolecular hydrogen bonds. Advanced imaging methods based on atomic force microscopy (AFM) have unravelled the morphological and mechanical heterogeneity of amyloids, however a full understanding has been hampered by the limited resolution of conventional spectroscopic methods. Here, it is shown that single molecule nanomechanical mapping and infrared nanospectroscopy (AFM‐IR) in combination with atomistic modelling enable unravelling at the single aggregate scale of the morphological, nanomechanical, chemical, and structural transition from amyloid fibrils to amyloid microcrystals in the hexapeptides, ILQINS, IFQINS, and TFQINS. Different morphologies have different Young's moduli, within 2–6 GPa, with amyloid fibrils exhibiting lower Young's moduli compared to amyloid microcrystals. The origins of this stiffening are unravelled and related to the increased content of intermolecular β ‐sheet and the increased lengthscale of cooperativity following the transition from twisted fibril to flat nanocrystal. Increased stiffness in Young's moduli is correlated with increased density of intermolecular hydrogen bonding and parallel β ‐sheet structure, which energetically stabilize crystals over the other polymorphs. These results offer additional evidence for the position of amyloid crystals in the minimum of the protein folding and aggregation landscape. Abstract : Atomic force microscopy, infrared nanospectroscopy, and atomistic modelling combined together allow elucidating the molecular origins of the exceptional thermodynamic stability of amyloid crystals, revealing the crucial role of the high density and order of intermolecular β ‐sheet associated with their purely translational symmetry and lack of mesoscopic twist of amyloid microcrystals.